HUKUM PIDANA ISLAM: PERSPEKTIF KEADILAN - Kun Budianto (Nurani, 2015)
Abstract: In social life required a legal system to create a harmonious society and regularly so that justice can be achieved. The legal system is very diverse, and that diversity in the legal system there are some that stand out. Western legal systems are represented by two systems, namely the civil law and common law, the legal system has been proved as the most widely adopted by many countries in the world. Another is the legal system of Islamic law. ملخص:في الحیاة الاجتماعیة یتطلب نظاما قانونیا لخلق مجتمع متناغم وبشكل منتظم بحیث یمكن تحقیق العدالة .ولذلك، وبطبیعة الحال سوف تحدید النظام القانوني وفقا لظروفھا .النظام القانوني ھي متنوعة جدا، وھذا التنوع في النظام القانوني ھناك بعض التي تبرز .یتم تمثیل النظم القانونیة الغربیة عن طریق النظامین، وھما القانون المدني والقانون العام، وقد ثبت النظام القانوني باعتبارھا الأكثر، والتراسل الذي اتخذه العدید من البلدان في العالم .آخر ھو النظام القانوني للشریعة الإسلامیة .كل من النظام القانوني ھو مركز الاھتمام في قلوب الفقھاء. Kata Kunci: hukum pidana islam, perubahan masyarakat